The last wish - Sapkowski, Andrzej (Gollancz London, 2019)
Introducing Geralt the Witcher - revered and hated - who holds the line against the monsters plaguing humanity in the bestselling series that inspired the Witcher video games and a major Netflix show.Geralt of Rivia is a Witcher, a man whose magic powers and lifelong training have made him a brilliant fighter and a merciless assassin.Yet he is no ordinary killer: he hunts the vile fiends that ravage the land and attack the innocent.But not everything monstrous-looking is evil; not everything fair is good . . . and in every fairy tale there is a grain of truth.Andrzej Sapkowski, winner of the World Fantasy Lifetime Achievement award, started an international phenomenon with his Witcher series. The Last Wish is the perfect introduction to this one-of-a-kind fantasy world.Alternate cover for this ISBN can be found here